A variable number of tandem repeats in the 3′‐untranslated region of the dopamine transporter modulates striatal function during working memory updating across the adult age span. (24th June 2015) - Sambataro, Fabio; Podell, Jamie E.; Murty, Vishnu P.; Das, Saumitra; Kolachana, Bhaskar; Goldberg, Terry E.; Weinberger, Daniel R.; Mattay, Venkata S.
Abstract Dopamine modulation of striatal function is critical for executive functions such as working memory (WM) updating. The dopamine transporter (DAT) regulates striatal dopamine signaling via synaptic reuptake. A variable number of tandem repeats in the 3′‐untranslated region of SLC6A3 (DAT1‐3′‐UTR‐VNTR) is associated with DAT expression, such that 9‐repeat allele carriers tend to express lower levels (associated with higher extracellular dopamine concentrations) than 10‐repeat homozygotes. Aging is also associated with decline of the dopamine system. The goal of the present study was to investigate the effects of aging and DAT1‐3′‐UTR‐VNTR on the neural activity and functional connectivity of the striatum during WM updating. Our results showed both an age‐related decrease in striatal activity and an effect of DAT1‐3′‐UTR‐VNTR. Ten‐repeat homozygotes showed reduced striatal activity and increased striatal–hippocampal connectivity during WM updating relative to the 9‐repeat carriers. There was no age by DAT1‐3′‐UTR‐VNTR interaction. These results suggest that, whereas striatal function during WM updating is modulated by both age and genetically determined DAT levels, the rate of the age‐related decline in striatal function is similar across both DAT1‐3′‐UTR‐VNTR genotype groups. They further suggest that, because of the baseline difference in striatal function based on DAT1‐3′‐UTR‐VNTR polymorphism, 10‐repeat homozygotes, who have lower levels of striatal function throughout the adult life span, may reach a threshold of decreased striatal function and manifest impairments in cognitive processes mediated by the striatum earlier in life than the 9‐repeat carriers. Our data suggest that age and DAT1‐3′‐UTR‐VNTR polymorphism independently modulate striatal function.